Eukaryotic translation initiation factor 4E binding protein 1 (EIF4EBP1) expression in glioblastoma is driven by ETS1- and MYBL2-dependent transcriptional activation - Hruby, Laura; Picard, Daniel; Musa, Julian; Remke, Marc; Grünewald, Thomas G. P.; Rotblat, Barak; Reifenberger, Guido; Leprivier, Gabriel (Cell death discovery, 2022)
Eukaryotic translation initiation factor 4E binding protein 1 (EIF4EBP1) encodes the 4EBP1 protein, a negative regulator of mRNA translation and a substrate of the mechanistic target of rapamycin (mTOR), whose function and relevance in cancer is still under debate. Here, we analyzed EIF4EBP1 expression in different glioma patient cohorts and investigated its mode of transcriptional regulation in glioblastoma cells. We verified that EIF4EBP1 mRNA is overexpressed in malignant gliomas, including isocitrate dehydrogenase (IDH)-wildtype glioblastomas, relative to non-neoplastic brain tissue in multiple publically available datasets. Our analyses revealed that EIF4EBP1 overexpression in malignant gliomas is neither due to gene amplification nor to altered DNA methylation, but rather results from aberrant transcriptional activation by distinct transcription factors. We found seven transcription factor candidates co-expressed with EIF4EBP1 in gliomas and bound to the EIF4EBP1 promoter, as revealed by chromatin immunoprecipitation (ChIP)-sequencing data. We investigated the ability of these candidates to activate the EIF4EBP1 promoter using luciferase reporter assays, which supported four transcription factors as candidate EIF4EBP1 regulators, namely MYBL2, ETS1, HIF-1A, and E2F6. Finally, by employing transient knock-down experiments to repress either of these transcription factors, we identified MYBL2 and ETS1 as the relevant transcriptional drivers of enhanced EIF4EBP1 expression in malignant glioma cells. Taken together, our findings confirm enhanced expression of EIF4EBP1 in malignant gliomas relative to non-neoplastic brain tissue and characterize the underlying molecular pathomechanisms.
Gesehen am 30.05.2022